ANALISIS MELODI DAN SYAIR MUSIK IRINGAN JEPIN TALI BINTANG DI DESA KALIMAS KALIMANTAN BARAT - Hawari, Yusran; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractJepin tali Bintang is one of many West Borneo (Kalimantan Barat) melayuâ€™s traditional dances, especialy in Kalimas Village, Sungai Kakap, Kubu Raya District. Formulation og the problem in this research is â€œHow is the motive of melody on the music background of Jepin Tali Bintang Dance?â€ , â€œhow does the meaning of the lyrics of the music background of Jepin Tali Bintang Dance?â€ and â€œHow does the design of the implementation of the study musicologi in the music background of Jepin Tali Bintang Kubu Raya in Highschool level?â€ This research was qualitative with musicology approach. The method that used in this study is analysis descriptive. In addition there is melodic motive system, the background music of jepin tali bintang dance also have a meaning there is the lyrics of background music of jepin tali bintang dance which contains an advice message and is intended as entertaiment. Besides it, the lyrics of the background music of jepin tali bintang dance give a message that is about the greatness of Allah SWT and invite muslims to know about the history and family tree or Prophet Muhammad SAW descendant.Â Â Keywords : Background Music of Jepin Tali Bintang Kalimas Village, Melody and Lyrics Motive